Dinamika perubahan kualitas air terhadap pertumbuhan ikan Lele Dumbo (Clarias gariepinus) yang dipelihara di kolam tanah. - Tania Serezova Augusta (Fakultas Peternakan Universitas Kristen Palangka Raya, 2016)
The aim of research to determine the dynamics of water quality to the growth of African catfish reared in earthen pond and to know the water quality that is suitable for the maintenance of African catfish. The method used in this research is the direct observation by collecting primary data directly from the field. Parameters measured were physical quality (temperature) and chemical quality (pH and DO) of pond water and length and weight measurements of African catfish to determine the absolute fish growth. The results showed that the water temperature of the pond ranging from 25 - 33oC. Dissolved oxygen ranged between 3.3 to 4.4 mg / l, and pH ranged from 6.4 to 9.15. Absolute growth rate of African catfish (by weight) was 109.39 grams, this means every month from June to August occurred 36.46 grams weight gain. During the study the fluctuations of temperature, pH and DO of pond water, do not effect on the growth of African catfish, this means that the water quality is decent enough for maintenance and rearing African catfish. Key words : Dynamics of water quality, African catfish, earthen pond.